Silicon chip-based quantum random number generator - Okawachi, Yoshitomo; Yu, Mengjie; Luke, Kevin; Carvalho, Daniel O. [UNESP]; Lipson, Michal; Gaeta, Alexander L. (My University, 2017)
We demonstrate an all-optical quantum random number generator using a degenerate optical parametric oscillator in a silicon-nitride microresonator. We achieve a 2-MHz generation rate and verify the randomness using the NIST Statistical Test Suite.